Efficiency of Northern pike (Esox lucius) stocking in metropolitan France at large spatial and temporal scales. (15th May 2021) - Guillerault, Nicolas; Loot, Géraldine; Blanchet, Simon; Millet, Paul; Musseau, Camille; Cucherousset, Julien; Santoul, Frédéric
Abstract: Stocking and electrofishing occurrence and abundance data for northern pike Esox lucius L. in >3800 km of French rivers across 7 years were compared to assess the effect of recreational fisheries stocking programmes on wild pike populations. A positive relationship was found between the additive effect of stocking and the size of the stocked pike. However, the stocking programmes implemented in France by recreational fishery managers from 2008 to 2013 increased the probability of pike occurring in the river network, without increasing abundance in well‐established pike populations, because pike stocked in their early‐life stages were used in most of the stocking programmes.